2011
DOI: 10.1007/s00520-011-1258-x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of radiotherapy-induced nausea and vomiting in the palliative treatment of bone metastases

Abstract: Despite prophylaxis, RINV was common among patients receiving palliative radiotherapy for bone metastases, especially during the delayed phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The lower results for the delayed phase were likely a result of the short half-life of ondansetron rdf (4-6 hours) which was taken mostly during the acute phase. Use of an ondansetron oral pill for the prophylaxis of rinv in patients has previously been reported 1,11,12 . Our group used the ondansetron 8 mg regular oral formulation for the prophylaxis of rinv and reported a complete control rate of 59% for nausea and 75% for vomiting 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower results for the delayed phase were likely a result of the short half-life of ondansetron rdf (4-6 hours) which was taken mostly during the acute phase. Use of an ondansetron oral pill for the prophylaxis of rinv in patients has previously been reported 1,11,12 . Our group used the ondansetron 8 mg regular oral formulation for the prophylaxis of rinv and reported a complete control rate of 59% for nausea and 75% for vomiting 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Use of an ondansetron oral pill for the prophylaxis of rinv in patients has previously been reported 1,11,12 . Our group used the ondansetron 8 mg regular oral formulation for the prophylaxis of rinv and reported a complete control rate of 59% for nausea and 75% for vomiting 1 . In another study by Presutti et al, the reported prophylaxis rate using the regular ondansetron 8 mg oral formulation for nausea during the acute phase was 54% in a singlefraction group and 67% in a multifraction group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of 5-HT 3 RAs for preventing nausea was, however, less pronounced, which make our high control rates notable. In the present study and in our reference pilot work 3 , we chose not to add dexamethasone to a 5-HT 3 RA because the inclusion of that option in the Multinational Association of Supportive Care in Cancer and American Society of Clinical Oncology guidelines stemmed from a single randomized trial 11 that enrolled patients receiving radiation therapy of a different duration and dose per fraction than our patients received. Moving forward, we also hope to establish an option for "add-on" therapy that will allow patients to avoid the potential toxicities of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported the results of a prospective cohort study demonstrating that, despite prophylaxis with a 5-HT 3 receptor antagonist (5-HT 3 RA) as recommended in international antiemetic guidelines 1,2 , radiotherapy-induced nausea and vomiting (rinv) was common in patients receiving moderately emetogenic radiotherapy alone for thoracolumbar bone metastases 3 . From the time of radiotherapy commencement until 10 days after radiotherapy completion, only 31% and 43% of patients receiving single-and multiplefraction radiotherapy respectively were free of nausea, and only 44% and 43% were free of vomiting.…”
Section: Introductionmentioning
confidence: 99%